Development of a virtual shapemeter based on a shape control model for continuous annealing. Issue 6 (19th February 2020) - L.V., Yu-Ting; Li, Yong; Yang, De-Xing; Bai, Zhenhua; Li, Jinlong; Wang, Rui
Abstract : Purpose: Continuous annealing (CA) units usually lack a physical shapemeter; consequently, real-time display and closed-loop control of the strip shape are impossible to achieve. Design/methodology/approach: A shape model for the CA process is established in this study. Specifically, a virtual shapemeter and closed-loop control system based on the advanced parameter acquisition system and information transmission of CA units are developed in C++ programming language. This system realises real-time dynamic shape display, closed-loop control and shape prediction by collecting raw data of steel coils and parameters during CA. Findings: Field test results show that the shape predicted by the virtual shapemeter coincides with the measured shape by over 90 per cent, which fully meets the precision requirement of industrial applications. Originality/value: Moreover, shape quality is effectively improved without increasing hardware investments.